DARI PISANG MENJADI PELUANG: STRATEGI PENINGKATAN USAHA KERIPIK DI SURABAYA - Aristyanto, Erwan; Abdillah, Khubbi; Hindratmo, Astria; Pratama, Adi Putra; Putra, Giovanni Firmansyah; Wawan, Yulianus (Universitas Muhammadiyah Gresik, 2024)
This PKM activity supports one of the main focus areas of Community Service 2024, namely the Green Economy sector in the use of composter tubes to process banana waste into fertilizer. The partner in this PKM is Mr. Sukri, owner of the JOYO banana chips business, located at Pakal Madya Jaya 5 no 11A RT 03 RW 02 Pakal Village, Pakal District, Surabaya City, which is 2.2 KM from the UWP campus. The urgency of this activity is low production capacity and the products produced are not good so it requires a touch of science and technology. The aim of this activity is to increase partner production capacity and quality and increase partner turnover. Priority problems, namely, in the Production sector, production equipment is still traditional and not ergonomic, wastes fuel, unhealthy and dirty inventory space and lots of rodents, workers do not wear PPE: Marketing sector, sales are unstable, packaging still uses thin plastic, labels and brands are less attractive, in the field of Business Management, there is no financial record keeping and there is no understanding of food health. The solution offered is to increase the quality and capacity of the business through developing banana chips TTG, increasing business capabilities, expanding marketing, improving packaging, labels and brands as well as financial records. Implementation method with TTG development of banana chips machine, partnership, training and mentoring. The results of the implementation of activities in this program include coordination of program implementation with partners, dissemination of TTG Banana Chips Machines, procurement of equipment and training on healthy production, dissemination of TTG Waste Processing Composter Tubes, online and offline sales training and assistance, training and assistance in making labels and logos , training and assistance in recording business financial transactions. The impact of this activity is an increase in the capacity and quality of partner products by 30%, an increase in partner turnover by 30%, an increase in partner knowledge and skills by 50%.